2022
DOI: 10.3390/brainsci12010079
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Quarantine on Pain Sensation among the General Population in China during the COVID-19 Pandemic

Abstract: During the pandemic era, quarantines might potentially have negative effects and disproportionately exacerbate health condition problems. We conducted this cross-sectional, national study to ascertain the prevalence of constant pain symptoms and how quarantines impacted the pain symptoms and identify the factors associated with constant pain to further guide reducing the prevalence of chronic pain for vulnerable people under the pandemic. The sociodemographic data, quarantine conditions, mental health situatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…There may be some explanations. Firstly, we speculate that one important reason why the psychological disorder of quarantined college students in this study was signi cantly higher than other groups is that the quarantine duration (48.83 ± 13.9 days) of these college students was much longer than participants who were usually only quarantined for one or two weeks in other investigations [24,31,32]. Another reason may be that the screening scales used to assess anxiety and depression are different.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…There may be some explanations. Firstly, we speculate that one important reason why the psychological disorder of quarantined college students in this study was signi cantly higher than other groups is that the quarantine duration (48.83 ± 13.9 days) of these college students was much longer than participants who were usually only quarantined for one or two weeks in other investigations [24,31,32]. Another reason may be that the screening scales used to assess anxiety and depression are different.…”
Section: Discussionmentioning
confidence: 69%
“…Moreover, long-term self-quarantine measures are associated with an increased risk of physical discomfort. Sun et al showed that long-term quarantine increased the risk of experiencing pain, and psychological symptoms could mediate the impact of the quarantine on pain symptoms [32]. In addition, Nakov et al reported that the prevalence of gastrointestinal symptoms signi cantly increased during the COVID-19 lockdown and may was associated increased numbers of patients with disorder of brain-gut interaction [4].…”
Section: Introductionmentioning
confidence: 99%